2020
DOI: 10.1186/s12920-020-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial tRNA methylation in Alzheimer’s disease and progressive supranuclear palsy

Abstract: Background: Methylation of mitochondrial tRNAs (mt-tRNA) at the 9th position ("p9 site") is known to impact translational efficiency and downstream mitochondrial function; however, direct assessment of mt-RNA methylation is challenging. Recent RNA sequence-based methods have been developed to reliably identify post-transcriptional methylation. Though p9 methylation has been studied in healthy human populations and in the context of cancer, it has not yet been analyzed in neurodegenerative disease, where mitoch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…3C ). In mammalian datasets, P9 methylation is required for correct folding, translational efficiency and downstream mitochondrial function of at least 11 of the mitochondrial tRNAs ( Silzer et al 2020 ). This modification may be representative of high metabolic activity in cumulus cells that is not present in oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3C ). In mammalian datasets, P9 methylation is required for correct folding, translational efficiency and downstream mitochondrial function of at least 11 of the mitochondrial tRNAs ( Silzer et al 2020 ). This modification may be representative of high metabolic activity in cumulus cells that is not present in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have used ultra-deep sequencing of mitochondrial RNA (mtRNA) have identified remarkable levels of sequence variation within individuals, as well as sites that show consistent patterns of post-transcriptional modification ( Hodgkinson et al 2014 , Bar-Yaacov et al 2016 ). Expression of nuclear-encoded genes potentially drives such modifications ( Hodgkinson et al 2014 , Silzer et al 2020 ). To our knowledge, there are no published RNA-seq data on oocyte mitochondrial transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of m1A methyltransferase leads to a more harmful AD phenotype [ 75 ]. Variable hypermethylation affecting the translation of downstream mitochondrial proteins was observed at the ninth position (p9) of mt-tRNA in cerebellar tissue after death in elderly AD patients, and a significant correlation between nuclear gene expression and p9 methylation was found [ 76 ]. mt-tRNA methylation may affect the expression of nuclear genes through retrograde signaling, but the mechanism behind this is unclear [ 77 , 78 ].…”
Section: Mitochondrial Epigenetic Changes In Admentioning
confidence: 99%
“… 76 Furthermore, variable methylation of mitochondrial tRNAs (mt-tRNAs) at 11 site in the ninth position (“p9 site”), which affects the efficiency of the translation as well as downstream mitochondrial function, was observed in PSP patients. 77 …”
Section: Role Of Epigenetic Processes In Pspmentioning
confidence: 99%